Eco-friendly synthesized nanoparticles as antimicrobial agents: an updated review - Borehalli Mayegowda, Shilpa; Roy, Arpita; N. G., Manjula; Pandit, Soumya; Alghamdi, Saad; Almehmadi, Mazen; Allahyani, Mamdouh; Awwad, Nasser S.; Sharma, Rohit (Frontiers in Cellular and Infection Microbiology, 2023)
Green synthesis NPs have gained extensive acceptance as they are reliable, eco-friendly and sustainable along with stability. Chemically synthesized NPs result in lung inflammation, heart problems, liver dysfunction, immune suppression, organ accumulation, and altered metabolism, leading to organ-specific toxicity. Biologically synthesised NPs from plants and microbes are biologically safe and cost-effective. These microbes and plant sources can consume and accumulate inorganic metal ions from their adjacent niche, synthesizing extracellular and intracellular NPs. These inherent characteristics of biological cells to process and modification of inorganic metal ions into NPs have helped to explore an area of biochemical analysis. Biological entities or their extracts used in NPs include algae, bacteria, fungi, actinomycetes, viruses, yeasts, and plants with varying capabilities through the bioreduction of metallic NPs. These biosynthesized NPs have a wide range of pharmaceutical applications like tissue engineering, detection of pathogens or proteins, antimicrobial agent, anticancerous mediators, vehicles for drug delivery, formulations for functional foods, identification of pathogens that can help to contribute to translational research in medical applications. These NPs have various applications in the food and drug packaging industry, agriculture, environmental remediation, etc.